ANALISIS BIAYA OPERASIONAL KENDARAAN (BOK) PADA PENGIRIMAN ENGINE CN-235 - Achmad Romadhoni; Aris Komara; Muchammad Fauzi (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2022)
PT Dirgantara Indonesia is a trusted center of excellence in the field of engineering, maintenance, repair and overhoul of gas turbine systems and rotating equipment leading in Southeast Asia. PT dirgantara Indonesia also carries out periodic maintenance that must be carried out by every owner who buys an aircraft at PT Dirgantara Indonesia, one of which is to carry out repairs, maintenance and overhouls on the engine, because engine overhoul repairs must be carried out at PT Nusantara Turbin and Propulsi, so they want to research vehicle operational costs (BOK) for the transfer of the engine from PT Dirgantara Indonesia to PT Nusantara Turbin and Propulsion or vice versa. The calculation is carried out by calculating fixed costs per year, calculating variable costs per year and calculating transport costs to get shipping rates based on dimensions and weight. From the calculation of the shipping cost based on dimensions of Rp. 61,824,100 / box and the basic shipping rate based on weight of Rp. 147,905 / kg. Berdasarkan hasil dan pembahasan diperoleh Biaya Tetap dan Biaya Variabel dengan jumlah sebesar Rp 190.228.000/forklift/tahun